Rancang Bangun Media Pembelajaran Interaktif Berbasis Prezi Materi Komponen Peta Pembelajaran IPS di Kelas V SD - Siti Zaqiyah; Tin Rustini; Dinie Anggraeni Dewi (Edumaspul: Jurnal Pendidikan, 2021)
Learning media is one of components in learning planning. Learning media is a learning process tool to deliver learning materials. Teacher can use concrete learning media directly, replica, or video, audio and image as an effort to deliver teaching materials more online/distance learning either synchronously/asynchronously, and of course learning media is becoming a very important component in delivering material. However, the use of learning media in fifth grade elementary school is still less varied in several subjects, one of which is social studies. The purpose of this research is to produce Prezi-based interactive learning media on social science learning map component material for fifth grade of elementary school. This research is a design and development research using the ADDIE model which consists of 5 stages (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation. The research instrument used is a questionnaire instrument. The validator questionnaire was used the assessment learning media by media experts and material experts. The response questionnaire was used to determine the user’s response i.e., 2 fifth grade elementary school teachers and 20 fifth grade elementary school students on Prezi-based interactive learning media on map component material for the fifth grade elementary school. The accumulated rating percentage of the validator is 89% and the accumulation of users is 87%. Thus, this learning media is very suitable to ne used in the map component of social studies learning material for the fifth grade of elementary school and can add variety use of learning media.